Surface charge effect on the cellular interaction and cytotoxicity of NaYF4:Yb3+, Er3+@SiO2 nanoparticles1. Issue 10 (6th February 2015) - Zhang, Junping; Liu, Fuyao; Li, Tao; He, Xiuxia; Wang, Zhenxin
<x xml:space="preserve">Abstract</x> The positively charged UCNP@SiO2-PEG-NH2 exhibits higher cytotoxicity and cellular internalization efficiency than negatively charged UCNP@SiO2-COOH and UCNP@SiO2-PEG.